The Effectiveness of PJBL-Based Learning Media in Enhancing Motivation and Outcomes of Grade XI Students at SMKN 1 Gunung Kijang Bintan - Syafrinal Syafrinal; Muhajir Muhajir; Nuril Huda (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study aims to measure the effectiveness of the use of Project-Based Learning (PjBL)-based learning media in improving the motivation and learning outcomes of grade XI students at SMKN 1 Gunung Kijang Bintan. The background of this research is the low motivation of students which has an impact on suboptimal learning outcomes, especially in subjects that require an in-depth understanding of concepts. PjBL is considered relevant because it provides students with the opportunity to be actively involved in real projects, potentially improving motivation and critical thinking skills. The method used is a quantitative research method with a correlational approach to test the relationship between learning motivation, the use of learning media, and student learning outcomes. The results showed that the use of PjBL-based learning media had a significant influence on student learning outcomes, while student learning motivation had no significant effect. These findings support the importance of interactive learning media in the learning process and suggest that the use of appropriate media can facilitate students' understanding of the material being taught.